Community-Based Intervention for Malnutrition in Children Under Five: A Scoping Review - Amelia, Vira; Arief, Yuni Sufyanti; Sylvia Dwi Wahyuni (Jurnal Berita Ilmu Keperawatan, 2025)
Malnutrition remains a significant global challenge, especially in developing countries. This scoping review aimed to identify community-based strategies for malnutrition in children under five. The scoping review conducted herein adhered to the methodologies outlined in conjunction with the guidelines specified in the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) extension for the scoping Reviews checklist. This study used three databases (PubMed, ProQuest, and Scopus) and included studies published between 2014-2024, with the search keywords "Intervention" or "Community-Based Intervention," “Children,” and “Malnutrition.” Results: Out of the 4846 identified articles, 11 studies were selected based on strict eligibility criteria. The results show that education, empowerment, supplementation, screening and monitoring, and other community-based interventions (home visits and meeting groups) contribute to malnutrition. The importance of community-based innovation in overcoming malnutrition in children can improve children's nutritional and health status. Program development includes increasing nutrition education, empowerment, providing adequate supplements, effective screening and monitoring to ensure the sustainability and effectiveness of community-based nutrition interventions.